(untitled) (One Health Journal of Nepal, 2024)
Health Management Information Systems (HMIS) are crucial in strengthening healthcare systems by providing data to inform policy, program design, and service delivery. In Nepal, HMIS data is collected across various health system levels; however, the extent to which this data is effectively utilized in decision-making still needs to be explored. This viewpoint examines the use of HMIS data within Nepal’s health sector and assesses its influence on health policies, resource allocation, and program implementation.